TEKNOLOGI KONVERSI ENERGI DAN BIOMASSA PERTANIAN BAGI RUMAH TANGGA DAN USAHATANI DESA TUTUR KABUPATEN PASURUAN - Sumargono, '; Mujoko, Tri; Sasongko, Edi (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
The "Manunggaling Karso" Farmer Group is a group of coffee farmers and dairy farmers based  in  Gunungsari sub-district, Tutur sub-district, chaired  by  Mr.  Winarso; with  a  total  of  31 members, and with a population of 575 dairy cows. In terms of the production of farming / livestock, as well as post-production it turns out that there are still quite crucial problems in the farmer group, namely  that  biogas products that  have  not  been  used  optimally  and  knowledge of  natural  plant medicines. For this reason, this service is focused on optimizing the use of biogas by purifying it first so that it can be used for lighting fuels. In addition, the presence of cow's urine that has not been used is used as an ingredient for biopesticides with natural ingredients found around Tutur village. The results that have been implemented include revamping the cow dung that is made slurry / mud which is then pumped into the digester. The gas produced is first purified so that it can be used for lighting using biogas-based petromax. The biogas obtained was detected with a blue flame and no smell. From the analysis of biogas after exiting from the purifier showed an increase in the methane gas content a nd a decrease in carbon dioxid gas, respectively from 35.02% to 68.5% and 25.26% to 19.83%.